Typification of thirteen names in Populus (Saliceae, Salicoideae, Salicaceae) - Zhang, Zhong-Shuai; Fu, Yun-Lei; Yu, Xi; Zhao, Tian-Bang; Zeng, Qing-Yin; Liu, Yan-Jing (Phytotaxa, 2024)
The article typified thirteen names of Chinese poplars which published by Zhao Tian-Bang or together with his cooperator in 1978 and 1980. By examining specimens preserved at PE, KUN, WUK, CAF, and HEAC, communication with Zhao Tian-Bang, we found that the original materials of Populus honanensis, P. funiushanensis, P. celtidifolia, P. davidiana var. lyshehensis, P. adenopoda var. nanchaoensis, P. adenopoda var. rotundifolia, P. hopeiensis var. ovatifolia, P. hopeiensis var. flavida, P. sunghoensis, P. davidiana var. longipetiolata, P. yunsiaoshanensis, and P. adenopoda var. microphylla were lost, and there was only one illustration left for P. tomentosa var. rotundifolia. According to the protologues, our fieldwork in the type localities and Zhao Tian-Bang’s identification, neotypes were designated for twelve taxa. An illustration was selected as the lectotype of P. tomentosa var. rotundifolia.